The Practice of Counted Prayers in Early Monasticism as a Form of Unceasing Synaxis - Viacheslav Patrin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The texts of early Egyptian monasticism contain information about the practice of counted prayers. In some cases, these counted prayers are presented as a form of incessant prayer. However, it is difficult to understand today what is meant in the Lausiac History by fifty, one hundred, three hundred, or seven hundred prayers. In the scientific literature, three respected scholars of the early monastic tradition – Adalbert Voguet, Gabriel Bunge, and Armand Veilleux – have formed the position that those counted prayers weren’t psalms and signify prayer moments or pauses during monastic manual labor. In our work we will present a critique of this position. Methods and analysis. On the basis of terminological and typological analysis of the prayer practice of Egyptian monks, we will give arguments that the counted prayers should be understood as exactly the psalms that were said in combination with prayers and that the counted prayers were the form of monastic synaxis performed separately from other activities. Results. Our study has shown that the counted prayers were an alternative way of realizing the idea of unceasing prayer in relation to the practice of the unceasing short prayer in the form of unceasing synaxis. In the period of early monasticism, the unceasing synaxis was practiced not only by the Euchite monks but also by the respected Egyptian ascetics. In the future, unceasing synaxis became the basis of the ascetic practice of the Acoemetae monks of Constantinople; therefore, our work in general may be useful for research on forms of unceasing prayer in Eastern monasticism.